Effects of Exogenous Putrescine on Delaying Senescence of Cut Foliage of Nephrolepis cordifolia - Qu, Ying; Jiang, Lu; Wuyun, Tana; Mu, Shouyuan; Xie, Fuchun; Chen, Yajun; Zhang, Lu (Frontiers in Plant Science, 2020)
Senescence is the main limitation for cut foliage display in vase. Naturally occurring polyamines such as putrescine (Put) have been considered effective anti-senescence agents. However, effect of Put on cut foliage in vase in a realistic indoor environment has not yet been revealed. In the present study, effects of Put spraying on the postharvest performance of cut foliage of Nephrolepis cordifolia L. were investigated. Cut fronds sprayed with deionized water (Put0) showed visible injuries after 10 days in vase. Meanwhile, chlorophyll (Chl), soluble protein (Sp), and proline (Pro) content were decreased by 60.15, 57.93, and 73.09% respectively, photochemical activity reflected by Chl fluorescence parameters was inhibited, whereas electrolyte leakage (EL), contents of soluble sugar (Ss), malondialdehyde (MDA), and hydrogen peroxide (H2O2) were increased (+194.29, +44.83, +34.06, and +178.01%, respectively). Put spraying extended the vase life of the cut foliage and the 2.0 mM Put had a longer vase life (21 days) than 0.2 mM (15 days). Leaf spraying of 2.0 mM Put for 10 days significantly ameliorated the losses of Chl, Sp, and Pro content (−10.72, −26.29, and −42.64%, respectively), followed by 0.2 mM Put (−27.36, −36.24, and −60.55%, respectively). Put spraying also improved photochemical capability and prevented membrane impairment as well as visible injury in comparison with Put0. In addition, 2.0 mM Put had a better mitigating ability than that of 0.2 mM. Leaf spraying of 2.0 mM Put greatly reduced the decline of the effective quantum yield of photochemical energy conversion in PSII (ΦPSII), the maximal quantum yield of PSII photochemistry measured in the dark-adapted state (Fv/Fm) and electron transport rate (ETR) (−7.89, −12.91, and −10.06%, respectively), and also inhibited the increases of EL, MDA, Ss, and H2O2 (+31.87, +6.43, +16.22, and +49.40%, respectively). Overall, Put played important roles in deterring the degradation of Chl, Ss, and Pro, detoxifying the H2O2, weakening the sugar signaling, mitigating the decline of photochemical activity, and eventually postponing the leaf senescence. The present study gives new insights into effects of Put on leaf senescence and provides a strategy for preserving post-harvest cut foliage.